Neural Proliferation and Restoration of Neurochemical Phenotypes and Compromised Functions Following Capsaicin-Induced Neuronal Damage in the Nodose Ganglion of the Adult Rat - Gallaher, Zachary R.; Ryu, Vitaly; Larios, Rose M.; Sprunger, Leslie K.; Czaja, Krzysztof (Frontiers in Neuroscience, 2011)
We previously reported that neuronal numbers within adult nodose ganglia (NG) were restored to normal levels 60 days following the capsaicin-induced destruction of nearly half of the neuronal population. However, the nature of this neuronal replacement is not known. Therefore, we aimed to characterize neural proliferation, neurochemical phenotypes, and functional recovery within adult rat NG neurons following capsaicin-induced damage. Sprague-Dawley rats received intraperitoneal injections of capsaicin or vehicle solution, followed by 5-bromo-2-deoxyuridine (BrdU) injections to reveal cellular proliferation. NG were collected at multiple times post-treatment (up to 300 days) and processed for immunofluorescence, RT-PCR, and dispersed cell cultures. Capsaicin-induced cellular proliferation, indicated by BrdU/Ki-67-labeled cells, suggests that lost neurons were replaced through cell division. NG cells expressed the stem cell marker, nestin, indicating that these ganglia have the capacity to generate new neurons. BrdU-incorporation within β-III tubulin-positive neuronal profiles following capsaicin suggests that proliferating cells matured to become neurons. NG neurons displayed decreased NMDAR expression up to 180-days post-capsaicin. However, both NMDAR expression within the NG and synaptophysin expression within the central target of NG neurons, the NTS, were restored to pre-injury levels by 300 days. NG cultures from capsaicin-treated rats contained bipolar neurons, normally found only during development. To test the functional recovery of NG neurons, we injected the satiety molecule, CCK. The effect of CCK on food intake was restored by 300-days post-capsaicin. This restoration may be due to the regeneration of damaged NG neurons or generation of functional neurons that replaced lost connections.